Eksplorasi Strategi Pembelajaran Bahasa Inggris di Kelas XI SMA Negeri 2 Bangli - Putu Lady Nova Kristina; Luh Made Dwi Wedayanthi (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Education is a very complex process that not only covers knowledge but also skills, including moral and ethical values. English as an international language has an important role in the field of education, especially in Indonesia at senior high school (SMA) with a focus on developing skills from speaking, listening, reading and writing. However, each learners have different abilities ranging from slow learners to fast learners, it requires teachers to apply a variety of learning strategies in accordance with learning. This study aims to explore English learning strategies applied at SMA Negeri 2 Bangli, especially in class XI. Through the descriptive qualitative research method, this study found that both teachers apply varied learning strategies according to the needs of students, and there are learning strategies that are rarely applied because they are considered less suitable for the characteristics and learning needs of students.